2020
DOI: 10.21203/rs.2.16869/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adjuvant chemotherapy could not bring survival benefit to HR-positive, HER2-negative, pT1b-c/N0-1/M0 invasive lobular carcinoma of the breast: a propensity score matching study based on SEER database

Abstract: Background : The benefit of adjuvant chemotherapy in invasive lobular carcinoma (ILC) is still unclear. The objective of the current study was to elucidate the effectiveness of adjuvant chemotherapy in hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative, pT1b-c/N0-1/M0 ILC. Methods: Based on Surveillance, Epidemiology, and End-Results (SEER) database, we identified original 12334 HR-positive, HER2-negative, pT1b-c/N0-1/M0 ILC patients, who were then divided into adjuvant ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…127 They did not identify a beneficial role for adjuvant chemotherapy with regard to overall survival (OS), in line with other literature. 37,[128][129][130][131] Most of the studies included in this meta-analysis did, however, not correct for ER, PR and HER2 and had a relatively short follow-up. A more recent US registry study that evaluated 17 789 patients with stage I-III ILC observed a similar OS after 5 years between patients receiving endocrine therapy alone and those receiving the combination of chemotherapy and endocrine therapy, after adjusting for age, stage, lymph node involvement, histology and radiotherapy.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…127 They did not identify a beneficial role for adjuvant chemotherapy with regard to overall survival (OS), in line with other literature. 37,[128][129][130][131] Most of the studies included in this meta-analysis did, however, not correct for ER, PR and HER2 and had a relatively short follow-up. A more recent US registry study that evaluated 17 789 patients with stage I-III ILC observed a similar OS after 5 years between patients receiving endocrine therapy alone and those receiving the combination of chemotherapy and endocrine therapy, after adjusting for age, stage, lymph node involvement, histology and radiotherapy.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…It has been demonstrated previously that ILC differs from IDC in its histopathology, genetic makeup, and pathophysiology and also in the characteristics of its patients and the treatment offered by clinicians 1,2,4,24,25 . Multiple studies have demonstrated that patients who have ILC are treated less often with CT compared with those who have similar tumor stage and IDC histology, with further studies questioning whether patients who have ILC derive any benefit from the addition of CT to their treatment 8,9,26,27 . The evolving myriad of genomic assays allows for more accurate and personalized patient care.…”
Section: Discussionmentioning
confidence: 99%
“…These tendencies may be explained by early trials demonstrating that patients with ILC had no advantage from the addition of CT to their treatment 8,9,26,27 . They may have been further influenced by findings that the RS had no prognostic value in patients with ILC.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative surgery is most appropriate for ILC when adequate preoperative investigations exclude multifocal and contralateral disease, and wider negative margins may not necessary for ILC [17]. Adjuvant chemotherapy may not improve survival for patients with HR(+)HER2(−) T1b-c/ N0-1/M0 ILC [18]. However, ILC patients could derive significant disease-free survival and OS benefits from chemotherapy, especially for high-risk patients [19].…”
Section: Discussionmentioning
confidence: 99%